(untitled) (Rev. Anal. Numér. Théor. Approx., 2009)
Book reviews for: Nicholas J. Higham, Handbook of Writing for the Mathematical Sciences, Second Ed., Philadelphia, 1998, ISBN 0-89871-420-6, XV + 302 pp. Reviewed by E. Catinas. L. Hodges, Jr. and E. L. Lehmann, Basic concepts of probability and statistics, Second Edition, SIAM, Philadelphia, PA, 2005, ISBN 0-89871-575-X, XX + 441 pp., Classics in Applied Mathematics, 48. Reviewed by E. Catinas. Thomas W. O’Gorman, Applied adaptive statistical methods. Tests of significance and confidence intervals, ASA, Alexandria, Virginia and SIAM, Philadelphia, Pennsylvania, 2004, ISBN 0-898715-53-9, XIII + 174 pp. Reviewed by E. Catinas. R. Peck, L.D. Haugh, A. Goodman, Statistical case studies. A collaboration between Academe and Industry, ASA, Alexandria, Virginia, and SIAM, Philadelphia, Pennsylvania, 1998, ISBN 0-89871-413-3, XXXI + 282 pp. Reviewed by E. Catinas. Jenny A. Baglivo, Mathematica laboratories for mathematical statistics. Emphasizing simulation and computer extensive methods, SIAM, Philadelphia, PA, 2005, ISBN 0-89871-566-0, XX + 260 pp. Reviewed by E. Catinas. John C. Strikwerda, Finite Difference Schemes and Partial Differential Equations, SIAM, Philadelphia, PA, 2004, ISBN 0-89871-567-9, XII + 434 pp. Reviewed by C. Revnic.